Ambient noise seismic reflection interferometry at the Los Humeros geothermal field, Mexico - Verdel, Arie (author); Boullenger, Boris (author); Martins, Joana E. (author); Obermann, Anne (author); Toledo Zambrano, Tania (author); Jousset, Philippe (author) (2019)
Integration of results from active seismic, passive seismic and well data reduces the uncertainties of several subsurface parameters that are of interest for cost-effective geothermal production operations in Los Humeros. In this study, we present results from the application of ambient noise seismic interferometry (ANSI) to retrieve zero-offset reflected P-waves from continuous seismic data recorded at the Los Humeros geothermal field, Mexico. This study is inspired by encouraging results from the application of ANSI for body wave reflection retrieval that was reported in 2016 for a geothermal field located at Reykjanes peninsula, Iceland (Verdel et al., 2016). Continuous broadband and short-period seismic recordings provided insightful reflection information that corresponded well, in relevant depth intervals, with reflectivity retrieved from the correlation of coda waves from a distant but very strong earthquake. That work was carried out within the context of EU’s Seventh Framework research and innovation program IMAGE. Encouraged by these findings, it was decided to conduct a new study following a similar approach within the context of the GEMex project, a European-Mexican collaboration. The purpose of GEMex is to gain an improved understanding of the geological structure and geothermal reservoir behaviour for two geothermal fields: Los Humeros and Acoculco. In the following, we address data selection and processing aspects related to the retrieval of reflected P-waves from Los Humeros seismic noise recordings. The retrieved reflections are compared with modelled reflectivities at two station locations at a close distance from the location where the seismic interval velocities that are used in the modelling were available from the literature. The reflected P-wave information provides structural detail about the field at locations directly underneath the employed seismic stations. Green Open Access added to TU Delft Institutional Repository ‘You share, we take care!’ – Taverne project ...